ANALISIS KOMPARATIF KINERJA EKONOMI USAHA AYAM NIAGA PEDAGING SISTEM KANDANG TERBUKA DAN KANDANG TERTUTUP DI KABUPATEN BANYUMAS - Febrianto, Benny Satria; Mastuti, Sri; Hidayat, Nunung Noor (ANGON: Journal of Animal Science and Technology, 2021)
Background. The purpose of this research is: 1). Analyzing the income and BEP of the broiler business with open house system and close house systems in Banyumas Regency, and 2. Examinig the difference between income and BEP for broiler business with open house system and close house systems in Banyumas Regency. Materials and Methods. The research was carried out by survey method, to determine the region using purposive random sampling method, is choose region Banyumas regency as a place for implementation of research because Banyumas Regency is one of the centers broiler bussines farm at Central Java. Next, to determine a sample of respondent using Stratified Random Sampling method the broiler business based on the housing sistem, is open house system as many as 31 farmer and close house system as many as 30 farmer. The research variables that observed were the number of livestock, production operational costs (total cost), production yields, and the price of broilers for the past year. Income were analyzed by using a cashflow, is difference of revenue and production cost, whereas break even point of the product is ratio between operational cost with volume product being produced and break even point of the price is ratio between operasional cost with prices of product. Income and break even point (BEP) were analyzed by using comparative analysis (t test) to determine the comparison with using Microsoft Excel. Results. The results of the analysis show that 1). the income 1000 broilers of the open house system is Rp. 3.626.578 and the closed house system is Rp. 4.896.844; BEP of the price and BEP of the products 1000 broilers of the open house system successively is Rp. 16,298/Kg and 1,901 Kg and close house system successively is Rp. 15,670/Kg and 1,853 Kg. 2). The result of comparative analisys show closed house system more profitable. The result shot that income and BEP of price is very significantly (P<0.01) and BEP of product is not significantly (P>0.05). Conclusion.The conclusion is close house system is more effective for broilers in feed consumption aspect, so its system could gain more income for the farmer, therefore we suggest the open house system farmer move to the closed house system if the circumstances are possible.